Human herpesvirus 6B origin-binding protein: DNA-binding domain and consensus binding sequence. - Inoue, N (1995)
We previously demonstrated by a DNA-binding assay that the human herpesvirus 6B (HHV-6B) replication origin has a structure similar to those of alphaherpesviruses, although the HHV-6B and herpes simplex virus type 1 (HSV-1) origin-binding proteins (OBPs) and origins are not interchangeable. Here we describe additional properties of the interaction between HHV-6B OBP and the HHV-6B origin. Competitive electrophoretic mobility shift assays (EMSAs) with DNA duplexes containing single-base alterations allowed deduction of a consensus DNA sequence for HHV-6B-specific OBP binding, YGWYCWCCY, where Y is T or C and W is T or A, while that for HSV-1-specific binding was reported to be YGYTCGCACT. By EMSA, the HHV-6B OBP DNA-binding domain was mapped to a segment containing amino acids 482 to 770. However, in Southwestern (protein-DNA) blotting, the region sufficient for the DNA binding encompassed only amino acids 657 to 770. Similarly, Southwestern blotting showed that amino acids 689 to 851 of HSV-1 OBP had HSV-1 origin-binding activity, although this region was insufficient for origin binding in the EMSA. Although the longer DNA-binding domains identified by EMSA have marginal overall homology among HHV-6B and alphaherpesvirus OBP homologs, the smaller regions sufficient for the binding observed by Southwestern blotting have significant similarity. From these results, we propose a hypothesis that the DNA-binding domain of herpesvirus OBPs consists of two subdomains, one containing a conserved motif that contacts DNA directly, and another, less well conserved, that may modulate either the conformation or accessibility of the binding domain.